2007
DOI: 10.5688/aj710469
|View full text |Cite
|
Sign up to set email alerts
|

Prepharmacy Years in College and Academic Performance in a Professional Program

Abstract: Objective. This study investigated whether there was a significant difference in the cumulative grade point average (GPA) of individual students at the end of their first 3 professional years in the doctor of pharmacy curriculum as a function of previous years in college. Methods. The cumulative GPA for the first-through third-professional years was calculated for the 2004-2007 graduating classes. Previous college education was classified as 2 years, 3 or more years without a bachelor's degree, and bachelor's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 3 publications
1
16
1
Order By: Relevance
“…17,18 Several other studies have found that pharmacy students with bachelor's degrees earned higher GPAs during their first year than did students with less prior education. [19][20][21][22][23][24] The findings reported in Table 3 are generally consistent with these previous studies, especially for students with a bachelor's degree, except with respect to the negative influence of student age. Regarding educational background data, neither candidates' last previous attendance at a 4-year college or a private school prior to matriculation nor parents' attainment of a bachelor's degree were significant factors in predicting first-year pharmacy students' GPAs.…”
Section: Multiple Regression Analysessupporting
confidence: 81%
“…17,18 Several other studies have found that pharmacy students with bachelor's degrees earned higher GPAs during their first year than did students with less prior education. [19][20][21][22][23][24] The findings reported in Table 3 are generally consistent with these previous studies, especially for students with a bachelor's degree, except with respect to the negative influence of student age. Regarding educational background data, neither candidates' last previous attendance at a 4-year college or a private school prior to matriculation nor parents' attainment of a bachelor's degree were significant factors in predicting first-year pharmacy students' GPAs.…”
Section: Multiple Regression Analysessupporting
confidence: 81%
“…4 Students who earn a bachelor's degree prior to entering a pharmacy program have higher cumulative grade point averages (GPAs) during the first year of the PharmD program than other students 5,6 ; however, the practical implications of a significant difference in GPA is questionable. 6 The association between student academic success and factors such as prepharmacy GPA, grades in specific prepharmacy courses, Pharmacy College Admission Test (PCAT) scores, and a prior 4-year college degree has been examined .…”
Section: Introductionmentioning
confidence: 99%
“…6 The association between student academic success and factors such as prepharmacy GPA, grades in specific prepharmacy courses, Pharmacy College Admission Test (PCAT) scores, and a prior 4-year college degree has been examined . [4][5][6][7][8][9][10][11] Cumulative prepharmacy GPA is an inconsistent predictor of academic success in pharmacy school. [12][13][14][15][16][17][18][19][20] Chisholm and colleagues reported a prior 4-year college degree as a predictor of success but the results of a study by Thomas and colleagues did not determine a prior degree as a predictor of success.…”
Section: Introductionmentioning
confidence: 99%
“…Predictors of academic success within pharmacy degree programs have included prepharmacy GPA and prepharmacy math/science GPA, 14,17,20,24 PCAT composite and PCAT subcategory scores, 18,20,21,25,27 and achievement of a 4-year college degree. 14,16,17,19,24,30 In contrast, some studies do not consider GPA as predictive, 14,16,18,19,23,27 some studies suggest use of the PCAT subcategory scores 10,15,20,22 over the PCAT composite score, and 1 study opposed the 4-year degree achievement as a predictor of success in pharmacy school. 22 Another study assessed factors related to advanced pharmacy practice experience (APPE) grades in doctor of pharmacy (PharmD) programs.…”
Section: Introductionmentioning
confidence: 99%